Analisis Kinerja Keuangan dengan Literasi Keuangan Syariah Sebagai Variabel Intervening - Nurul Astutik; Anna Widiastuti (Inovbiz: Jurnal Inovasi Bisnis, 2020)
Micro, Small and Medium Enterprises (MSMEs) have an important role for a country's economic development in addition to being able to absorb labor as well as its contribution to Gross Domestic Product (GDP), where MSMEs are the largest informal sector driver in Indonesia. One of the concerns of many countries is from the financial literacy that is owned, but for this research the sharia financial literacy dimension is used. This study aims to analyze the financial performance of ikat weaving in Troso Jepara through determinants namely  hopelessness, religiosity and financial satisfaction with intervening Islamic financial literacy. Primary data were obtained from the results of questionnaire responses submitted to 88 respondents and analyzed with SPSS. Determination of the number of samples using the Slovin formula with the Incindental Sampling technique. The results of the study found that hopelessness did not affect islamic financial literacy, while religiosity influenced islamic financial literacy at MSMEs, while financial performance was only financial satisfaction variables that had an influence on performance improvement at MSME Weaving Ikats in Jepara Regency